Perception of Risk of Exposure to Covid-19 and Quality of Life for Nurses in the Emergency Room after Booster Vaccination - Diki Ardiansyah; Balqis Fashila; Wisdom Rudiyana; Theresia Avila Kurnia; Muhamad Jauhar (Poltekkes Kemenkes Semarang, 2023)
Background: nurses' perceptions of risk have an impact on the process of dealing with a pandemic as well as affecting their quality of life in terms of physical health, psychology, social relations, and the environment.Purpose: this study analyzed the relationship between perceptions of the risk of exposure to Covid-19 and the quality of life of nurses in the Emergency Room after booster vaccination.Methods: research using studies cross-sectional by sampling technique total sampling for all emergency room nurses at hospitals in Sukabumi City there were 49 people. The data collection instrument uses a risk perception questionnaire and a questionnaireWorld Health Organization Quality of Life (WHOQOL-BREF).Results: the result revealed that51% had high-risk perception and 51% had poor physical health, 63.3% had bad psychological, 57.1% had a bad environment, and 77.6% with good social relations. After doing the testChi-Square significance (α = 0.05), there is a relationship between perceptions of the risk of exposure to Covid-19 with 3 domains of quality of life including physical health (0.032), psychological (0.029), and the environment (0.029). But there is no relationship with the domain of social relations (0.196).Conclusion: Health workers, especially nurses, always have a good coping mechanism during a pandemic. Apart from that, it is hoped that nurses can improve their quality of life, such as maintaining their physical and psychological health to improve the quality of service.